CLEC14A protects against podocyte injury in mice with adriamycin nephropathy. Issue 7 (9th June 2021) - Su, Zeyu; Li, Yujia; Lv, Hang; Cui, Xiaoyang; Liu, Min; Wang, Ziying; Zhang, Yan; Zhen, Junhui; Tang, Wei; Wang, Xiaojie; Yi, Fan
Abstract: Podocyte injury is a major determinant of focal segmental glomerular sclerosis (FSGS) and the identification of potential therapeutic targets for preventing podocyte injury has clinical importance for the treatment of FSGS. CLEC14A is a single‐pass transmembrane glycoprotein belonging to the vascular expressed C‐type lectin family. CLEC14A is found to be expressed in vascular endothelial cells during embryogenesis and is also implicated in tumor angiogenesis. However, the current understanding of the biological functions of CLEC14A in podocyte is very limited. In this study, we found that CLEC14A was expressed in podocyte and protected against podocyte injury in mice with Adriamycin (ADR)‐induced FSGS. First, we observed that CLEC14A was downregulated in mice with ADR nephropathy and renal biopsies from individuals with FSGS and other forms of podocytopathies. Moreover, CLEC14A deficiency exacerbated podocyte injury and proteinuria in mice with ADR nephropathy accompanied by enhanced inflammatory cell infiltration and inflammatory responses. In vitro, overexpression of CLEC14A in podocyte had pleiotropic protective actions, including anti‐inflammatory and anti‐apoptosis effects. Mechanistically, CLEC14A inhibited high‐mobility group box 1 protein (HMGB1) release, at least in part by directly binding HMGB1, and suppressed HMGB1‐mediated signaling, including NF‐κB signaling and early growth response protein 1 (EGR1) signaling. Taken together, our findings provide new insights into the pivotal role of CLEC14A in maintaining podocyte function, indicating that CLEC14A may be an innovative therapeutic target in FSGS.